USING BLOGS IN TEACHING TERTIARY ESL WRITING - Romualdo A. Mabuan (English Review: Journal of English Education, 2018)
Anchored on the Technological, Pedagogical and Content Knowledge or TPACK Framework (Koehler Mishra, 2009) and Substitution, Augmentation, Modification and Redefinition or SAMR Model of Technology Integration into the classroom (Puentedura, 2014), this study investigated a corpus of 58 blog posts written by ESL learners through weblogs. It aimed to determine the views of students on the use of blogs in learning English writing skills and to explore students’ feedback on the advantages of blogging as a virtual writing platform. Research participants were 58 freshman university tourism students enrolled at a Study and Thinking Skills class in a private university in Manila, the Philippines during the first semester of the academic year 2017-2018. Research data drawn from students’ blogs, survey questionnaires and focus group discussion revealed that despite accessibility issues due to technological resources, the learners viewed blogging as a viable platform in learning English writing skills because it affords them freedom to express their thoughts, it develops or improves their writing skills, and it allows them to connect and engage with their peers online, inter alia. Pedagogical implications for ESL writing teachers and researchers are offered based on these results.Keywords: Teaching writing, ESL writing, weblogs, blogging, TPACK, SAMR